Soil nutrient condition related to the distribution of terrestrial algae near Syowa Station, Antarctica (extended abstract) - Akiyama, Masaru; Ohyama, Yoshikuni; Kanda, Hiroshi (1986)
P(論文) departmental bulletin paper